South America - Oachs, Emily Rose (Minneapolis, MN : Bellwether Media, Inc., 2016)
Simple text and full-color photography introduce beginning readers to South America.
Largest rain forest -- Where is South America? -- The land and climate -- The plants and animals -- The people -- Fast facts about South America -- Glossary -- At the library.
Includes bibliographical references and index.
K-3
3.3
Keywords: South America